Numerical simulations of combustion instability in Rijke-Zhao tube - Liu, Xiaoyang. (2013)
In this report, a numerical model is developed to investigate the combustion instability in a Rijke-Zhao tube. This study is carried out in an attempt to better understand the internal coupling among pressure and velocity oscillations and heating element changes. Combustion instabilities or oscillations occur in confined geometries and are caused by the interactions between unsteady heat release and acoustic waves [1-4]. However, instabilities occur if the phase shifts between the pressure and heat flux is less than ±90 degree [5]. For a given combustion system, when the Rayleigh criterion [19] is satisfied, the unsteady heat release rate will be increased by amplified pressure fluctuations, and the oscillation amplitude will grow until it reaches the limit cycle.